Pelatihan Penggunaan Sosial Media Pada Usaha Pande Besi di Desa Kedisan–Gianyar - Ni Kadek Nita Noviani Pande; Christina Purnama Yanti; Komang Redy Winatha; Ni Luh Wiwik Sri Rahayu Ginantra (JPM: Jurnal Pengabdian Masyarakat, 2020)
Balinese handicrafts are also a worldwide attraction. For example, handicrafts from wood carvings, paintings, endek fabrics, keris, gamelan, copper, gold, silver, and many more. Keris and gambelan in Bali are generally made by the Pande people or you can say Soroh Pande and the manufacturing process is done in a Prapen. Prapen is always identified with cheer pande, apart from being a place for people to do their swadharma, namely memande. Prapen itself is very important for the Pande people not only as their identity as a Pande but also as a livelihood for Pande residents to work which has been passed down by their ancestors from generation to generation. In Kedisan Kaja Village, Tegalalang District, Gianyar Regency, there is a Small and Medium Enterprise (UKM) group that is engaged in memande. The business that has been going on for years only uses a pre-order system (making when there is an order). Based on the results of the interview, the main problems experienced by the partners, namely (1) their knowledge of product marketing is still very limited, and (2) they do not have a storage place for memande completeness. The purpose of this PKM is to increase the understanding and skills of partners in the form of product marketing techniques. The method used in achieving this goal is the use of technology by holding training on the use of Instagram and Facebook social media to improve marketing so that craftsmen can market their handicrafts on social media independently and be able to increase sales